BS EN 60383-1 Ed.5.0. Insulators for overhead lines with a nominal voltage above 1000 V. Part 1. Ceramic or glass insulator units for a.c. systems. Definitions, test methods and acceptance criteria (22nd December 2020) - British Standards Institution
No abstract available